SENAM OTAK LEBIH MENINGKATKAN KESEIMBANGAN DINAMIS DARIPADA SENAM KESEGARAN JASMANI (2008) PADA ANAK USIA 7-8 TAHUN DI KECAMATAN SIMPANG TERITIP BANGKA BARAT - Siamy, Hapy Ardiaviandaru; Pangkahila, J.Alex; Irfan, Muh. (Sport and Fitness Journal, 2015)
Nowadays , decreasing of physical activity of children were increasing the risk of falling and injury. The Provision of physical activity of children years will increase the balancing ability and reduced risk of fall. Dinamic balance started at age 7-8 years. Gymnastics is a physical activity which helps to optimize the brain function, one of them is dynamis balance. This study aims to determine the physical training of brain gyms were better to improve the dynamic balancing than Senam Kesegaran Jasmani (SKJ) 2008 in children of age 7-8 years old.This study used true experimental method with pre-test and post design. Experiment was conducted in SD Negeri 8 Simpang Teritip, SD Negeri 11 Simpang Teritip, SD Negeri 15 Simpang Teritip Bangka Barat. Group control was given intervention SKJ 2008 consisted of 38 boys and 41 girls, while in the treatment group was given brain gyms intervention consisted of 35 boys and 44 girls. The exercises was conducted 3x per week for 6 weeks. Balance beam walking test was used to measure the dynamic balancing. The results of using Wilcoxon test in the control group gained an average of dynamic balancing before trained the SKJ 2008 was 2.95 ± 0.354 and after trained the SKJ 2008 was 4.15 ± 0.949 with p = 0.000 (p <0.05). Whereas in the treatment group the mean of dynamic balance before brain gym was 2.89 ± 0.358 and after brain gym was 4.97 ± 0.225 with p = 0.000 (p <0.05). Different mean of dynamic balancing among group control and treatment were tested using the Mann Whitney was obtained p value = 0.000 (p <0.05) with a mean value of dynamic balance after treatment in the treatment group of brain gym was 4.97 ± 0.225 was heigest than the group of SKJ 2008 was 4.15 ± 0.949. The conclusion of SKJ 2008 and brain gyms that can improve the dynamic balancing in children of age 7-8 years old, however brain gym was more improve the dynamic balance than SKJ 2008 in children of age 7-8 years old.
Keywords: Brain Gym, SKJ 2008, Dynamic Balance, Balance Beam Walking Test